Answer:
D. (x – 3)^2 = 17
Step-by-step explanation:
We assume you want an equivalent to x^2 -6x = 8.
We can complete the square by adding the square of half the x-coefficient to both sides of the equation.
x^2 -6x +(-6/2)^2 = 8 +(-6/2)^2
(x -3)^2 = 17 . . . . simplify
Answer:
1/3 =0.33
Step-by-step explanation:
<em>ju</em><em>st</em><em> </em><em>subst</em><em>itute</em><em> </em><em>the</em><em> </em><em>va</em><em>lues</em><em> </em><em>of</em><em> </em><em>x</em><em> </em><em>and </em><em>y</em><em> </em><em>int</em><em>o</em><em> </em><em>th</em><em>e</em><em> </em><em>exp</em><em>ression</em><em> </em><em>to</em><em> </em><em>get</em>
<em>4</em><em>(</em><em>2</em><em>)</em><em>+</em><em>1</em><em> </em><em>/</em><em>3</em><em>(</em><em>3</em><em>)</em><em>^</em><em>2</em>
<em>=</em><em>8</em><em>+</em><em>1</em><em> </em><em>/</em><em>3</em><em>×</em><em>9</em>
<em>=</em><em>9</em><em>/</em><em>2</em><em>7</em>
<em>=</em><em>1</em><em>/</em><em>3</em>
<em>=</em>0.33
Answer:
5.75
Step-by-step explanation:
4) 230 ÷ 40 = 5.75